Analisa Perbedaan Kinerja Akibat Dampak Perubahan Teknologi Pada Unit International Roaming - Tendy Arya (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2020)
PT XYZ gave a mandate to the international roaming unit to deal with overseas telecommunications business problems. International roaming units are required to optimize the performance of technology adoption. The data used are secondary data from the company while the method used is descriptive, BSC and pair test. The result is that international roaming units need to optimize technology adoption.